Slr0320 Is Crucial for Optimal Function of Photosystem II during High Light Acclimation in Synechocystis sp. PCC 6803 - Hao Zhang; Haitao Ge; Ye Zhang; Yingchun Wang; Pengpeng Zhang (Life, 2021)
Upon exposure of photosynthetic organisms to high light (HL), several HL acclimation responses are triggered. Herein, we identified a novel gene, slr0320, critical for HL acclimation in Synechocystis sp. PCC 6803. The growth rate of the Δslr0320 mutant was similar to wild type (WT) under normal light (NL) but severely declined under HL. Net photosynthesis of the mutant was lower under HL, but maximum photosystem II (PSII) activity was higher under NL and HL. Immunodetection revealed the accumulation and assembly of PSII were similar between WT and the mutant. Chlorophyll fluorescence traces showed the stable fluorescence of the mutant under light was much higher. Kinetics of single flash-induced chlorophyll fluorescence increase and decay revealed the slower electron transfer from QA to QB in the mutant. These data indicate that, in the Δslr0320 mutant, the number of functional PSIIs was comparable to WT even under HL but the electron transfer between QA and QB was inefficient. Quantitative proteomics and real-time PCR revealed that expression profiles of psbL, psbH and psbI were significantly altered in the Δslr0320 mutant. Thus, Slr0320 protein plays critical roles in optimizing PSII activity during HL acclimation and is essential for PSII electron transfer from QA to QB.